Influence of knee positions on torque and myoelectric activity of triceps surae at maximum isometric plantar flexion - Baptista, Marco Túlio; Nascimento, Francisco Xavier Monteiro do; Nardes, Leandro Kegler; Matta, Thiago Torres da; OLIVEIRA, Liliam Fernandes de (Brazilian journal of physical education and sport, 2014)
The aim of this study was to compare the maximum torque of plantar flexors using two knee positions and analyze the mioelectric activity variation of the muscles in both conditions. The sample was composed of 14 healthy men. The participants were positioned on the dynamometer with the right foot attached to the adapter in neutral position (ankle at 90º). Two five seconds of two consecutives maximum isometric voluntary contractions were obtained for each knee position: full extended and 90o. The gastrocnemius lateralis (GNL), medialis (GNM) and soleus RMS value of eletomyography signal and the plantar flexor peak torque average were acquired during three intermediate seconds. The average torques in the knee positions of extension and flexion were 100.4 ± 17.4 Nm and 72.6 ± 18.4 Nm respectively. With the knee flexed, the gastrocnemius presented a decreased activation (40.5 ± 10.5 e 31.7 ± 25.6% for lateral and medial, respectively) while the soleus showed an increased (35.6 ± 28.9%). The reduction of torque appears to result from a compromise between the inhibition of myoelectric activity of the gastrocnemius medialis and lateralis, while the soleus activation is optimized. The results may contribute to exercise prescription plantar flexors muscles emphasizing the different muscles activation varying the knee position.